Use Of Complementary And Alternative Medicines Among Cancer Patients In Penang, Malaysia: A Qualitative And Quantitative Assessment Of Health Beliefs, Treatment Disclosure And Health Related Quality Of Life - Farooqui, Maryam (2013)
The use of Complementary and Alternative Medicines (CAM) is widespread for general health maintenance and management of disease symptoms. In Malaysia, there is evidence that a variety of CAM is used by patients with cancer. Cancer patients tend to use CAM in an attempt to reduce cancer recurrence and to lessen the side effects due to conventional therapies. The study aimed to provide a comprehensive evaluation of health beliefs, treatment disclosure and health related quality of life of cancer patients in the context of CAM. A mixed methodological approach using both qualitative and quantitative methods was adapted. The thematic content analysis identified three major themes: patients’ beliefs towards cancer and its treatment, patients’ perceptions toward the use of CAM for cancer treatment and the disclosure of CAM use to the health care providers. Twenty patients were interviewed, twelve of them reported to use CAM while only four disclosed it to the doctors. The slow progression of CAM effectiveness and cost were given as barrier to CAM use. Patients agreed that CAM disclosure is important to avoid any interaction with the conventional medicines.